Fulvestrant 500 mg Versus Anastrozole 1 mg for the First-Line Treatment of Advanced Breast Cancer: Overall Survival Analysis From the Phase II FIRST Study - Ellis, Matthew J; Llombart-Cussac, Antonio; Feltl, David; Dewar, John A; Jasiówka, Marek; Hewson, Nicola; Rukazenkov, Yuri; Robertson, John F R (Journal of clinical oncology, 2015)
PURPOSE: To compare overall survival (OS) for fulvestrant 500 mg versus anastrozole as first-line endocrine therapy for advanced breast cancer. PATIENTS AND METHODS: The Fulvestrant First-Line Study Comparing Endocrine Treatments (FIRST) was a phase II, randomized, open-label, multicenter trial. Postmenopausal women with estrogen receptor-positive, locally advanced/metastatic breast cancer who had no previous therapy for advanced disease received either fulvestrant 500 mg (days 0, 14, 28, and every 28 days thereafter) or anastrozole 1 mg (daily). The primary end point (clinical benefit rate [72.5% and 67.0%]) and a follow-up analysis (median time to progression [23.4 months and 13.1 months]) have been reported previously for fulvestrant 500 mg and anastrozole, respectively. Subsequently, the protocol was amended to assess OS by unadjusted log-rank test after approximately 65% of patients had died. Treatment effect on OS across several subgroups was examined. Tolerability was evaluated by adverse event monitoring. RESULTS: In total, 205 patients were randomly assigned (fulvestrant 500 mg, n = 102; anastrozole, n = 103). At data cutoff, 61.8% (fulvestrant 500 mg, n = 63) and 71.8% (anastrozole, n = 74) had died. The hazard ratio (95% CI) for OS with fulvestrant 500 mg versus anastrozole was 0.70 (0.50 to 0.98; P = .04; median OS, 54.1 months v 48.4 months). Treatment effects seemed generally consistent across the subgroups analyzed. No new safety issues were observed. CONCLUSION: There are several limitations of this OS analysis, including that it was not planned in the original protocol but instead was added after time-to-progression results were analyzed, and that not all patients participated in additional OS follow-up. However, the present results suggest fulvestrant 500 mg extends OS versus anastrozole. This finding now awaits prospective confirmation in the larger phase III FALCON (Fulvestrant and Anastrozole Compared in Hormonal Therapy Naïve Advanced Breast Cancer) trial (ClinicalTrials.gov identifier: NCT01602380).
Keywords: dospělí; Aromatase Inhibitors; hormonální protinádorové látky; Triazoles; nádory prsu; přežití bez známek nemoci; Disease-Free Survival; Humans; lidé středního věku; inhibitory aromatasy; Middle Aged; Kaplanův-Meierův odhad; Breast Neoplasms; antagonisté estrogenového receptoru; Nitriles; Antineoplastic Agents, Hormonal; Adult; Estrogen Receptor Antagonists; výsledek terapie; Drug Administration Schedule; Estradiol; Treatment Outcome; ženské pohlaví; rozvrh dávkování léků; nitrily; lidé; estradiol; triazoly; Aged; senioři; Kaplan-Meier Estimate; Female